2015
DOI: 10.1007/s00125-015-3616-6
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermographic assessment of changes in skin temperature during hypoglycaemia in patients with type 1 diabetes

Abstract: Aims/hypothesis Hypoglycaemia is associated with reduced skin temperature (Ts). We studied whether infrared thermography can detect Ts changes during hypoglycaemia in patients with type 1 diabetes and how the Ts response differs between patients with normal hypoglycaemia awareness and hypoglycaemia unawareness. Methods Twenty-four patients with type 1 diabetes (ten aware, 14 unaware) were studied during normoglycaemia (5.0-6.0 mmol/l), hypoglycaemia (2.0-2.5 mmol/l) and during recovery from hypoglycaemia (5.0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Sejling et al . found that there is a decrement in skin temperature during hypoglycaemia, and that this decrement is less in IAH patients 20 . Circumstances that could affect a participant’s temperature include the hand/arm-warmer, placement of the sensor and the ambient temperature in the room.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sejling et al . found that there is a decrement in skin temperature during hypoglycaemia, and that this decrement is less in IAH patients 20 . Circumstances that could affect a participant’s temperature include the hand/arm-warmer, placement of the sensor and the ambient temperature in the room.…”
Section: Discussionmentioning
confidence: 93%
“…Sejling et al . 19 , 20 have previously investigated people with IAH during hypoglycaemic clamp, and compared their responses with people with normal hypoglycaemia awareness. Sweating and ECG-changes were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that the shoulder is just not a good place to measure temperature differences. Sejling et al found that the nose experienced the largest temperature fall (178), although hardly a good place for a temperature sensor. It may be that larger variations exist during sleep, and provide even more information for an alarm algorithm, which potentially can be explored later.…”
Section: Predicting Blood Glucose Levels and Trendsmentioning
confidence: 99%
“…Diabetes not only leads to changes in skin structure, but also in skin components, such as variation of epidermal and dermal features [2], as well as nerve fiber loss [1,6]. Some studies show that diabetes induces skin dysfunctions like reduced skin barrier functions [7], changes in mechanical properties of dermal collagen fibril [8], mechanical hyposensitivity and abnormal temperature of skin [9,10]. In addition, the abnormal changes in motor behavior of skin immune cells or skin microvascular function occur with the development of diabetes [11,12].…”
Section: Introductionmentioning
confidence: 99%